2003
DOI: 10.1016/j.actamat.2003.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Ambient to high-temperature fracture toughness and cyclic fatigue behavior in Al-containing silicon carbide ceramics

Abstract: Abstract-A series of in situ toughened, Al, B and C containing, silicon carbide ceramics (ABC-SiC) has been examined with Al contents varying from 3 to 7 wt%. With increasing Al additions, the grain morphology in the as-processed microstructures varied from elongated to bimodal to equiaxed, with a change in the nature of the grain-boundary film from amorphous to partially crystalline to fully crystalline. Fracture toughness and cyclic fatigue tests on these microstructures revealed that although the 7 wt.% Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 33 publications
(51 reference statements)
1
41
1
1
Order By: Relevance
“…The substantially enhanced toughness in the 5ABC-SiC was associated with extensive crack bridging from both interlocking grains, as in 3ABC-SiC, and uncracked ligaments, which only occurred in 5ABC-SiC. No toughening by crack bridging was apparent in 7ABC-SiC, concomitant with a transition from intergranular to transgranular fracture [32].…”
Section: Effects Of Additive Contentmentioning
confidence: 91%
“…The substantially enhanced toughness in the 5ABC-SiC was associated with extensive crack bridging from both interlocking grains, as in 3ABC-SiC, and uncracked ligaments, which only occurred in 5ABC-SiC. No toughening by crack bridging was apparent in 7ABC-SiC, concomitant with a transition from intergranular to transgranular fracture [32].…”
Section: Effects Of Additive Contentmentioning
confidence: 91%
“…Many studies have reported the control of its microstructure in order to improve the sinterability, mechanical properties, etc., using many kinds of additives. [1][2][3][4][5] Several studies have reported that the sinterability and the mechanical properties of the SiC were improved by colloidal processing, 6-10 because the colloidal processing is generally able to control the dispersion of powders in a suspension and to produce a fine and dense microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…18) Likewise, the fracture toughness of the SiCAl 8 B 4 C 7 was believed to be improved partly due to the similar chemical composition of Al 8 B 4 C 7 with the AlBC.…”
Section: )11)mentioning
confidence: 99%
“…Yuan et al reported that an amorphous phase composed of SiO 2 and the AlBC could be fully crystallized during cooling down and the crystallization behavior was affected by the chemical composition of the AlBC. 18) The beneficial effect of phenolic resin on the densification of the SiCAl 8 B 4 C 7 was believed to be caused by promoting the rearrangement of SiC particles. Phenolic resin pyrolized into carbon below 1200°C during sintering.…”
Section: )11)mentioning
confidence: 99%